2017
DOI: 10.1371/journal.pone.0180161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance profiles of cerebrospinal fluid pathogens in children with acute bacterial meningitis in Yunnan province, China, 2012-2015

Abstract: Acute bacterial meningitis is still considered one of the most dangerous infectious diseases in children. To investigate the prevalence and antibiotic resistance profiles of cerebrospinal fluid (CSF) pathogens in children with acute bacterial meningitis in Southwest China, CSF samples from 179 meningitis patients (3 days to 12 years old) with positive culture results were collected from 2012 to 2015. Isolated pathogens were identified using the Vitek-32 system. Gram stain results were used to guide subcultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

27
55
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 32 publications
27
55
4
Order By: Relevance
“…One isolates of H. influenzae b showed lower rate of resistance to ciprofloxacin and ceftriaxone. This is in line with study in china that reported lower rate resistance to ciprofloxacin and ceftriaxone (35).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…One isolates of H. influenzae b showed lower rate of resistance to ciprofloxacin and ceftriaxone. This is in line with study in china that reported lower rate resistance to ciprofloxacin and ceftriaxone (35).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the predominant cause of bacterial meningitis among under-five children was S. pneumoniae (34.2%), this is similar with study conducted in China where S. pneumoniae was reported to be the predominant isolate (35). This finding of the present study could be supported by study conducted in Gonder, in Addis Ababa and in Jimma which reported that the predominant isolates was S. pneumoniae 70%, 35.3% and 50% respectively (28,36,37).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…are showed (50.8%) acute bacterial meningitis in pediatric caused GPB infections. 25 Zhu et.al. are found GPB predominant pathogen in pediatric patients caused purulent meningitis were E. coli and Staphylococcus spp.…”
mentioning
confidence: 99%